2020
DOI: 10.1016/j.parepi.2019.e00125
|View full text |Cite|
|
Sign up to set email alerts
|

Determination of subtypes of Blastocystis sp. in Chilean patients with and without inflammatory bowel syndrome, A preliminary report

Abstract: Background & methodsBlastocystis sp. is one of the most prevalent unicellular eukaryote of the human large intestine in Chile and worldwide. It is classified in subtypes (STs), where using the polymorphic sequences of its 18S rRNA genes currently recognizes 22. STs 1–9 and ST12 have been reported in humans. It has been hypothesized that different STs of Blastocystis sp. differentially affect the clinical severity of the digestive disease in Irritable Bowel Syndrome (IBS) patients, but more studies ar4e needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…These findings are similar to previous reports in Turkey, Iran, and Mexico, where subtypes 1, 2, and 3 were found in patients with IBS [ 51 , 52 , 53 ]. Additionally, another study in Chile, reported that Blastocystis subtypes 1, 2, and 4 are related to IBS [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to previous reports in Turkey, Iran, and Mexico, where subtypes 1, 2, and 3 were found in patients with IBS [ 51 , 52 , 53 ]. Additionally, another study in Chile, reported that Blastocystis subtypes 1, 2, and 4 are related to IBS [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In South America, there have been some studies focused on this protozoon [ 2 , 16 , 17 , 18 ], with only one study of Blastocystis subtypes in Peru [ 7 ]. However, Blastocystis infection has been reported in some Peruvian cities [ 19 , 20 , 21 ] and Arequipa has had the highest prevalence levels with 48.3% in elementary school children and 81.9% in low-income communities [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent microbiome studies indicated that this parasite can colonize the human gut for long periods of time without provoking symptoms [ 8 ] and that Blastocystis carriers have higher bacterial diversity than non- Blastocystis carriers [ 9 11 ], suggesting that it should be considered a commensal rather than a pathogen. In contrast, other studies suggested that Blastocystis is commonly associated with irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD) [ 12 , 13 ]. However, most of these studies have not thoroughly analyzed the etiological role of Blastocystis in the development of IBS or IBD and, in fact, some IBS and IBD patients are not Blastocystis carriers, which in itself should cast doubt on the etiological role of Blastocystis in these syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Blastocystis sp. has been found in patients with irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD), [ 17 , 18 ], but not the presence of the protist that causes them. In vitro experiments using cell lines have also determined the potential pathogenicity of some specific STs of Blastocystis sp., such as disrupting the epithelial barrier [ 19 ] by increasing the epithelial permeability [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%